2008
DOI: 10.1111/j.1461-0248.2008.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent competition can compromise the safety of highly specific biocontrol agents

Abstract: Despite current concern about the safety of biological control of weeds, assessing the indirect impacts of introduced agents is not common practice. Using 17 replicate food webs, we demonstrate that the use of a highly host-plant specific weed biocontrol agent, recently introduced into Australia, is associated with declines of local insect communities. The agent shares natural enemies (predators and parasitoids) with seed herbivore species from native plants, so apparent competition is the most likely cause fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 38 publications
1
95
0
Order By: Relevance
“…More generally, it would be one of the first observed cases of an invasive herbivorous insect indirectly affecting native herbivores that do not share the same resource. To our knowledge, the only other convincing case is that of Carvalheiro et al (2008), who observed that an introduced seed feeder affects native communities of seed herbivores in Australia. Leaf miners are ideal models to study apparent competition between alien and native species because, firstly, leaf miners are among the most successful invaders and become particularly abundant compared to native species (Godfray et al 1995;Girardoz et al 2007c); secondly, because leaf miners share many polyphagous natural enemies, particularly parasitoids (Askew 1994;Memmott et al 1994;Morris et al 2004); and, thirdly, because leaf miners are easy to sample and parasitism can be easily assessed using standard methods (Girardoz et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, it would be one of the first observed cases of an invasive herbivorous insect indirectly affecting native herbivores that do not share the same resource. To our knowledge, the only other convincing case is that of Carvalheiro et al (2008), who observed that an introduced seed feeder affects native communities of seed herbivores in Australia. Leaf miners are ideal models to study apparent competition between alien and native species because, firstly, leaf miners are among the most successful invaders and become particularly abundant compared to native species (Godfray et al 1995;Girardoz et al 2007c); secondly, because leaf miners share many polyphagous natural enemies, particularly parasitoids (Askew 1994;Memmott et al 1994;Morris et al 2004); and, thirdly, because leaf miners are easy to sample and parasitism can be easily assessed using standard methods (Girardoz et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…Settle and Wilson (1990) showed that the invasion of the variegated leafhopper, Erythroneura variabilis in California led to the decline of its native congener E. elegantula, and that this decline was correlated with increased levels of a shared egg parasitoid. More recently, Carvalheiro et al (2008) reported evidence that a seed feeder introduced as weed biological control agent may affect populations of several seed herbivores in Australia through apparent competition.…”
Section: Introductionmentioning
confidence: 99%
“…Such structuring has been revealed in a range of systems (Forbes, Powell, Stelinski, Smith, & Feder, 2009; Hood et al., 2015; Smith, Wood, Janzen, Hallwachs, & Hebert, 2007; Smith et al., 2008; Stireman et al., 2006). More broadly, understanding how insect herbivores and parasitoid communities are structured has implications for many aspects of ecosystem management, including biological control of herbivorous pests (Carvalheiro, Buckley, Ventim, Fowler, & Memmott, 2008; Henneman & Memmott, 2001), and predicting the impacts of range expansions associated with anthropogenic introductions and climate change (Nicholls, Fuentes‐Utrilla, et al., 2010; Sax et al., 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The possibility of host specific biocontrol agents creating deleterious collateral impacts within native arthropod communities has been documented elsewhere (e.g., United States of America; Callaway 2003, 2005;and Australia;Carvalheiro et al 2008). Host specific weed biocontrol agents can indirectly compete with native arthropod herbivores on their nearby host plants if the two herbivores share natural enemies (i.e., apparent competition; Holt 1977) (Carvalheiro et al 2008).…”
Section: Agricultural Inputs and Practices: Abiotic Factors That Affementioning
confidence: 99%